CONCENTRATIONS OF HEAVY METALS (Cr, Cuand Zn) IN DIFFERENT SIZE OF BLOOD COCKLE Anadara granosa FROM GEMURUH VILLAGE COASTAL WATER OF KUNDUR ISLAND KARIMUN REGENCY, RIAU ISLANDS PROVINCE. - Agnesia Jaiyani br Barus; Bintal Amin; Yusni Ikhwan Siregar (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
The research was conducted in March 2017 by collecting samples of blood cockles (Anadara granosa) from Gemuruh Village Island coastal waters of Kundur Island, Karimun Regencyof Riau Islands Province. The study used survey method and the samples were collected from the intertidal area directly by hand. The resultsof this study showed that Cr content was found to be highest in medium size of the cockle in Station 1(0,7850μg/g), the highest Cu content was found in small size in Station 1(1,4983μg/g), and the highest Zn content was found in medium size in Station 2(24,9517μg/g). The results also showed that MPI values obtained from Gemuruh Village coastal waters was 2,0472. PTWI calculation derived from stations for Cr was 15,3374 mg/kg of body weight per week, Cu amounted to 1045,2839 mg/kg of body weight per week, whilst for Zn amounted to 2203,2374 mg/kg of body weight per week for the average of 70kg body weight. The concentrations of heavy metals in cockles from Gemuruh Village coastal waters can be considered as safe and accordingly there is no risk for the human consumption of these species as long as it does not exceed the suggested limit.Key words: Heavy metal, Anadara granosa, PTWI, Kundur Island